Agreement between the United Kingdom of Great Britain and Northern Ireland and Japan concerning the Facilitation of Reciprocal Access and Cooperation between the Self-Defense Forces of Japan and the Armed Forces of the United Kingdom of Great Britain and Northern Ireland, London, 11 January 2023. ([2023-02-20]) - Unknown
No abstract available